(untitled) (International Journal of Environmental Sciences, 2025)
In order to fulfil the demand for a smooth, effective, and inclusive payment system and to completely transform the digital payments environment, the Unified Payments Interface was established in India. UPI has registered 8,572 crore transactions in the current fiscal year as of December 11, 2023. It has been a major contributor to the rise of online payments in India, which represented 62% of these transactions in FY 2022–2023. Approximately 581 Indian banks were using the UPI as of April 2024. As of now, there fails to be a reliable study methodology for gauging user acceptance of UPI. Thus, this study presents a thorough analysis of recent research on consumers’ intentions to use mobile and online payments and develops a novel model specifically for determining the adoption determinants of "Unified Payment Interface (UPI)". The model was presented in the paper by adding to the UTAUT2 model that was already in place by integrating, " Interoperability," " Observability," and " Perceived Trust " represent novel constructs. Further empirical testing of the suggested model may yield significant results and recommendations that help those who offer payment services make the right choices for the growth of their customer base.